Grammatical Errors Made by Eighth-Grade Students in Speaking English - Anggraini, Merliyani Putri; Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2021)
This research primarily deals with grammatical error analysis. It describes the grammatical errors in speaking skills made by the eighth-grade students. The data of the study are the conversation of the students that are defined into ten groups. The grammatical errors are classified based on Comparative Taxonomy. They are; developmental errors, interlingual errors, ambiguous errors, and other errors. Besides classifying the errors, the research also discovers the sources of errors. A qualitative approach was employed to gather the data in this study. The result of this study shows that the students committed errors in every type of Comparative Taxonomy. The most error that students made was interlingual errors. It can be inferred that the student's mother tongue interfered with them in speaking English. Based on the observation and interview, the possible causes of students' grammatical errors were interlingual transfer, intralingual transfer, the context of learning, and communication strategy.